2020
DOI: 10.1016/j.jcbs.2020.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effect of IBS acceptance on psychosocial mediators of Irritable Bowel Syndrome

Abstract: Background/Objective: In this study a theoretically driven model is presented of how gastrointestinal anxiety, behavioural response, symptom severity, quality of life and IBS acceptance interact to determine how people cope and respond in IBS. Method: Crosssectional data from 166 outpatients attending a motility disorders clinic was used to test a model of moderated serial mediation. Results: Gastrointestinal anxiety and behavioural response were found to serially mediate the relationship between symptom sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In light of these notes, it is possible to say that the current study might be more representative of the experience of patients with IBD and more robust in its findings given that it accounts for more related variables. It is, however, encouraging that as a process variable, GSA seems to have a similar role in the development of problems with QoL as observed in IBS populations [35]; it can be specifically targeted through several types of psychological interventions (e.g., [36]).…”
Section: Discussionmentioning
confidence: 87%
“…In light of these notes, it is possible to say that the current study might be more representative of the experience of patients with IBD and more robust in its findings given that it accounts for more related variables. It is, however, encouraging that as a process variable, GSA seems to have a similar role in the development of problems with QoL as observed in IBS populations [35]; it can be specifically targeted through several types of psychological interventions (e.g., [36]).…”
Section: Discussionmentioning
confidence: 87%
“…The mechanism by which ACT may help patients with IBS may be due to acceptance of symptoms. Bowers and colleagues ( 41 ) conducted a secondary data analysis of Gillanders and colleagues ( 39 ) and Ferreira and colleagues ( 38 ) studies and concluded that IBS acceptance may mediate and moderate IBS QOL. The authors hypothesize that participants with IBS who have more IBS acceptance engage in less avoidant behaviors (i.e., more values-based behavior) and thus see less of an impact on their QOL ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…Bowers and colleagues ( 41 ) conducted a secondary data analysis of Gillanders and colleagues ( 39 ) and Ferreira and colleagues ( 38 ) studies and concluded that IBS acceptance may mediate and moderate IBS QOL. The authors hypothesize that participants with IBS who have more IBS acceptance engage in less avoidant behaviors (i.e., more values-based behavior) and thus see less of an impact on their QOL ( 41 ). IBS acceptance may be protective even if symptom severity is high, which is consistent with literature on ACT in other chronic health conditions ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations